Thermo Elasto-Plastic Analysis of Rotating Axisymmetrical Bodies Using Modified Von-Mises Yield Criterion - Hussain, Imad A.; Lafta, Hameed D.; Hussain, Rafa’a D. (Al-Khwarizmi Engineering Journal, 2019)
In the present work, the behavior of thick-walled cylinder of elasto-plastic material (polymeric material) has been studied analytically. The study is based on modified Von-Mises yield criterion (for non metallic material). The equations of stress distribution are obtained for the cylinder under general cases of elastic expansion, plastic initiation and elastic-plastic expansion. A computer program is developed for evaluating the stress distribution. The solution is carried out for worst boundary conditions when the cylinder is subjected to the combination of pressure load, inertia load, and temperature gradient. The results are presented graphically in terms of dimensionless stresses and radius ratio. They indicate that the thermal and rotational loads are greatly influencing the stress distribution and the initiation of plastic zone, as well as the spreading out of the plastic zone. Moreover, it was found that the critical values of loads required for starting plastic deformation are determined by the amount of the applied load and the type of loading conditions, and it is found that the variation of stresses are greatly influenced by increasing of the temperature gradient at constant pressure and inertial loads than other increases in loading conditions.